Inhibition of Under-Deposit Corrosion of Carbon Steel by Thiobenzamide - Pandarinathan, Vedapriya; Lepkova, Katerina; Bailey, Stuart; Gubner, Rolf (The Electrochemical Society, Inc, 2013)
The inhibition performance of thiobenzamide (TB) against the under deposit corrosion of carbon steel in CO2-saturated, chloride-containing environment has been investigated. TB concentrations were varied from 10 - 200 ppm and temperature from 30 degrees centigrade to 60 degrees centigrade were tested. TB effectively inhibits corrosion at carbon steel surfaces with and without sand deposits, reducing the general corrosion rates below 0.1 mm y-1 in all cases studied. Electrochemical tests results sugest that inhibition occurs via adsorption at the steel surface through the S atom of the TB molecule. Potentiodynamic polarization measurements show that the inhibition mechanism differs at surfaces with and without sand deposits with temperature change over the range of 30 degrees centigrade to 60 degrees centigrade. Surface analysis of the corroded steels showed that general corrosion takes place at surfaces without sand deposits, whereas localized corrosion proceeds at the surfaces underneath a sand deposit, both in the presencea and absence of thiobenzamide.